Online Professional Skills Workshops: Perspectives from Distance Education Graduate Students - Gauvreau, Sarah; Hurst, Deborah; Cleveland-Innes, Martha; Hawranik, Pamela (International Review of Research in Open and Distributed Learning, 2016)
While many online graduate students are gaining academic and scholarly knowledge, the opportunities for students to develop and hone professional skills essential for the workplace are lacking. Given the virtual environment of distance learning, graduate students are often expected to glean professional skills such as analytical thinking, self-awareness, flexibility, team-building, and problem-solving inherently through informal means (Cleveland-Innes & Ally, 2012). The goal of this study was to evaluate the experiences of online graduate students participating in synchronous online professional skills workshops. Students attended the sessions from the various graduate programs at an online Canadian university. The discussions from the focus group held at the end of the project were used to achieve the research goals. This paper used a phenomenological lens to accomplish its research goals. The participants reported that they experienced a “sense of community” and learned skills that were not included in their academic programs.